Strengthening Governance for Farmers’ Occupational Health Efforts: Impact on Target Achievement in Kolaka Regency - Haerun, Haerun; Saafi, La Ode; Sunarsih, Sunarsih (Waluya The International Science of Health Journal, 2025)
Introduction: This study examines the factors influencing the achievement of occupational health targets for farmers in Kolaka Regency, focusing on health literacy, health facility accessibility, health service improvement, and farmer group participation. Conducted from February to July 2023, it involved 213 informal farmers across several sub-districts, using structured interviews and direct observation for data collection. Method: This study is quantitative with a Cross-Sectional Study design, providing a brief and representative snapshot of the population's condition during a certain period. The study population comprised 455 members of farmer groups in Kolaka Regency. The sample was determined using the Slovin formula, resulting in a sample size of 213 people. Result: The findings indicate significant relationships between health literacy (p=0.000; φ=0.594) and health facility accessibility (p=0.000; φ=0.689) with achieving health targets. However, health service improvement (p=0.000; φ=0.290) and farmer group participation (p=0.000; φ=0.514) showed weaker correlations. The majority of respondents reported no improvement in health literacy (58.22%), accessibility of health facilities (59.15%), health services (59.62%), and farmer group participation (59.15%). Furthermore, 59% stated that occupational health targets were not achieved. Conclusion: The study recommends that the Kolaka Regency Regional Government allocate an adequate budget for occupational health programs and improve access to health facilities. The Health Office should enhance health literacy programs and facility accessibility, particularly in remote areas.